The Role of Interfirm Knowledge Spillovers for Innovation in Mass-Produced Environmental Technologies: Evidence from the Solar Photovoltaic Industry. (March 2018) - Hoppmann, Joern
Knowledge spillovers play a potentially important role for innovation and competitive dynamics in mass-produced environmental technologies. Currently, however, we lack research that studies knowledge spillovers in such technologies at the firm level. To address this shortcoming, in this article we investigate the drivers of technological innovation in the solar photovoltaic industry. We find clear evidence for the existence of interfirm knowledge spillovers and show that besides investments in R&D, investments in manufacturing equipment have served as a channel of knowledge absorption. Our findings shed new light on the narrative linking environmental innovation and competitive advantage. Moreover, by pointing to the role of process technology as a means of assimilating and exploiting external knowledge, we highlight an important but frequently neglected channel of absorptive capacity.